A different approach to the treatment of the lateral malleolar fractures with syndesmosis injury: the ANK nail. - Kara, A N; Esenyel, C Z; Sener, B T; Merih, E (My University, 2023)
This retrospective study was conducted on a total of 139 cases of fractured ankles involving the fibula above the syndesmosis which were treated with open reduction and internal fixation with the intramedullary ANK nail at the Department of Orthopaedic Surgery at Vakif Gureba Teaching Hospital from 1990 to 1997. We were able to review 128 of these patients after a mean follow-up of 3.1 years (range, 1 - 7 years) including 60 with Weber type B and 68 with Weber type C fractures. The results were evaluated using objective, subjective, and roentgenographic criteria described by Cedell. Ninety-three patients (73%) have obtained good objective results, 28 (22%) fair, and seven (5%) have obtained poor objective results. Subjective rating were 94 patients (74%), good; 26 patients (20%), fair; and eight patients (6%), poor. Good radiological results were found in 99 patients (77%), fair radiological results in 21 patients (17%), and poor radiological results were found in eight patients (6%). It is concluded that the ANK nail could be used for the fixation of the lateral malleolar fracture with tear of the syndesmosis ligament.